PENDEKATAN SISTEM DALAM ADMINISTRASI PUBLIK: KERANGKA PEMIKIRAN BERBASIS INPUT–PROCESS–OUTPUT–FEEDBACK–ENVIRONMENT (IPOFE) - Engkus, Engkus (Jurnal Governansi, 2026)
Public administration faces complex and increasingly dynamic public policy and service issues. However, in many public administration studies, the framework used is still partial, thus failing to systematically explain the relationship between public demands, decision-making processes, policy outcomes, and environmental influences. This study aims to formulate and analyze a public administration framework based on a systems approach through the components of input, process, output, feedback, and environment (IPOFE). This study employed a qualitative approach with a conceptual design through a literature review method of various primary sources in the field of public administration and public policy, including both classic books and reputable scientific journal articles. The analysis was conducted through stages of literature selection, thematic analysis, and conceptual synthesis. The results show that the systems approach is able to explain public administration as an open system involving interactions between public demands as input, administrative and political processes in decision-making, policy outputs as output, feedback mechanisms as policy evaluation, and the influence of the social, political, and economic environment. The integration of these five components strengthens the analysis of public policy and services in a more comprehensive, contextual, and adaptive manner. The novelty of this research lies in the development of the IPOFE conceptual framework as a systemic analysis model that can be used in public administration studies to understand the dynamic relationship between policy processes, public services, and the government environment.